Audit of A Web-Based Electronic Documents and Record Management System (WEDRMS): Oversight Efforts to Improve Administration in Higher Educational Institutions - Richatul Jannah; Fitrarena Widhi Rizkyana; Risanda Alirastra Budiantoro (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
An electronic records had important role in organizations including a university or higher educational institutions. It was important to stay abreast of best practices and new technologies to manage these records effectively. A Web-Based Electronic Documents and Records Management System (WEDRMS) was a web-based system that was expected to reach a wide range of system users. This system had functions to store, archive and retrieve electronic documents. The purpose of this research was to explain further an audit implication for Web-Based Electronic Documents and Record Management System (WEDRMS) as an effort to supervise administration of higher educational Institutions. This research used a descriptive research approach with observation and document analysis for the data collection process. With the existence of an audit, it can become an alternative to managing electronic documents in the higher education environment. This research provides perspective and urgency regarding the audit implication of web-based electronic documentation dan recording management.